1997
DOI: 10.2337/diab.46.12.2119
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Increases Hypothalamic Pro-opiomelanocortin mRNA Expression in the Rostral Arcuate Nucleus

Abstract: Melanocortins are peptides, cleaved from the pro-opiomelanocortin (POMC) precursor, that act in the brain to reduce food intake and are potential mediators of leptin action. In the forebrain, melanocortins are derived from POMC-containing neurons of the hypothalamic arcuate nucleus. To test the hypothesis that these POMC neurons are regulated by leptin, we used in situ hybridization to determine whether reduced leptin signaling (as occurs in fasting), genetic leptin deficiency (in obese ob/ob mice), or genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
327
2
6

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(350 citation statements)
references
References 30 publications
15
327
2
6
Order By: Relevance
“…Up-regulation of POMC mRNA contrasts with the widely described down-regulation of anorexigenic neuropeptides during food restriction (Schwartz et al, 1997) and is probably a result of a unique situation of limited food access along with physical activity. Previously, we observed that physical activity per se does not result in up-regulation of POMC gene expression (Hillebrand et al, 2005c;.…”
Section: Discussionmentioning
confidence: 76%
“…Up-regulation of POMC mRNA contrasts with the widely described down-regulation of anorexigenic neuropeptides during food restriction (Schwartz et al, 1997) and is probably a result of a unique situation of limited food access along with physical activity. Previously, we observed that physical activity per se does not result in up-regulation of POMC gene expression (Hillebrand et al, 2005c;.…”
Section: Discussionmentioning
confidence: 76%
“…POMC can be differentially cleaved by proteases to generate an array of hormones (adrenocorticotrophic hormone [ACTH], lipotropin, corticotrophin-like intermediate peptide [CLIP], melanocyte-stimulating hormone [MSH] and β-endorphin) that exert multiple effects crucial in linking the organism's metabolic state to its reproductive capacity. The expression of POMC mRNA is significantly reduced by CR implemented upon rats, mice and also primates (Bergendahl et al, 1992;Koegler et al, 2001;Schwartz et al, 1997;Mizuno et al, 1998). The proteolytic cleavage products themselves of POMC have differential effects on the reproductive axis, e.g.…”
Section: Pro-opiomelanocortinmentioning
confidence: 99%
“…For example, most of POMC-expressing Arc neurons coexpress Ob-Rb mRNA. 73 Leptin increases POMC mRNA in the Arc 74 and induces the expression of c-fos and SOCS-3 mRNA in Arc POMC neurons. 65,66 In addition, POMC mRNA in the Arc is markedly reduced in leptin-deficient ob/ob mice as well as in fasted rodents (when leptin levels rapidly fall).…”
mentioning
confidence: 97%
“…75,76 The decrease in POMC expression is prevented by leptin administration. [74][75][76] Finally, leptin directly depolarizes POMC neurons. 69 Of importance, a-MSH acts as an agonist for the melanocortin-4 receptor (MC4-R), 70,77,78 a Gs-proteincoupled receptor distributed in the CNS.…”
mentioning
confidence: 98%